Discrimination of various cosmetic products using ATR-FTIR spectroscopy and chemometrics - Ismail, Nur Syuhada (2025)
In today’s world, cosmetics have become an essential part in our everyday lives. Cosmetic products can serve as valuable evidence at crime scenes, as cosmetic smudges fall under the category of transfer evidence. The contact between a cosmetic user (whether victim or perpetrator) and objects or other individuals often results in the transfer of cosmetic residues, which can help link individuals to specific locations, events, or interactions. Furthermore, there has been limited forensic studies focus on analysis for discrimination of different types of cosmetic products. In this study, Attenuated Total Reflectance-Fourier Transform-Infrared (ATR-FTIR) spectroscopy, a rapid and non-destructive has been utilised to differentiate a total of 16 cosmetic products of four different types. Principal Component Analysis-Linear Discriminant Analysis (PCA-LDA) was employed to complement visual spectral comparisons and generate objective interpretation of the results. 100 % accuracy of predictive PCA-LDA model was established with all samples regardless of cosmetic types were correctly classified to their respective brands. The blind test was conducted with three unknown samples, which were correctly linked with their respective source. In persistence study, selected cosmetic products were exposed at room temperature and aged samples for up to 12 hours still showed similar spectral features similarly to their fresh samples that allowed identification. The current work demonstrated a quick, cost-effective, robust, and non-destructive method for differentiation of various cosmetic products in forensic investigation